Dating the termination of the Palaeoproterozoic Lomagundi-Jatuli carbon isotopic event in the North Transfennoscandian Greenstone Belt - Martin, A. P.; Condon, D. J.; Prave, Tony; Melezhik, V. A.; Lepland, A.; Fallick, A. E. (Precambrian Research, 2013)
Existing radio-isotopic age constraints indicate that the global Palaeoproterozoic Lomagundi-Jatuli large, positive carbonate carbon isotopic excursion, with delta C-13 values >+5 parts per thousand, occurred between 2.2 and 2.06 Ga. In the North Transfennoscandian Greenstone Belt of the Kola Peninsula, NW Russia, northern Norway and Finland, the Lomagundi-Jatuli Event is recorded in the carbonate rocks of the Umba and Kuetsjarvi Sedimentary Formations in the Imandra-Varzuga and Pechenga greenstone belts. In both areas, thick mafic volcanic units (Umba and Kuetsjarvi Volcanic Formations) overlie the carbon isotopic excursion-bearing sedimentary units. Overlying and younger sedimentary units contain carbonate rocks with delta C-13 values typically ranging between c. -1 and +3 parts per thousand, signalling the termination of the Lomagundi-Jatuli excursion. Two new U-Pb ID-TIMS (isotope-dilution thermal ionisation mass spectrometry) zircon dates constrain this termination in both successions. The lower unit of the Il'mozero Sedimentary Formation is a cross- and parallel-bedded volcaniclastic greywacke derived largely from erosion of the underlying Umba Volcanic Formation. It has yielded detrital zircons with Pb-207/Pb-206 dates as young as 2055.5 +/- 2.3 Ma, which is a maximum age for deposition and is inferred to date part of the underlying Umba volcanics. In Pechenga, the Kolosjoki Sedimentary Formation was intersected by a drill hole obtained by the ICDP (International Continental Scientific Drilling Program)-supported FAR-DEEP (Fennoscandian Arctic Russia-Drilling Early Earth Project) drilling programme. Zircons from a mafic fine tuff in this drill core have yielded a Pb-207/Pb-206 age of 2056.6 +/- 0.8 Ma. This age is interpreted as an eruption age contemporaneous with sedimentation. The new age determinations overlap each other within uncertainty, and is within error of previously published detrital zircon ages of 2058 +/- 2 Ma from the Kolosjoki Sedimentary Formation and 2049 +/- 28 Ma from the ...